Examining Discursive Representations of Transformation, Identity, and Exclusion in Kafka’s The Metamorphosis: A Study through Discourse Analysis - Muhammad Usman Arshad (`, 2025)
This research analyzes the discursive representations of change, identity, and exclusion in Franz Kafka’s The Metamorphosis using discourse analysis. The aim of the study was to examine how language creates alienation, undermines self-identity, and perpetuates discriminatory behaviors inside the story. The study’s foundation emphasizes Kafka’s tale as a pivotal modernist work that reveals the tenuous connection between the person and society, especially via Gregor Samsa’s transformation into an insect. A mixed-methods approach was used, integrating qualitative discourse analysis (thematic, contextual, and critical analysis) with quantitative techniques (lexical frequency and pronoun tracking). The study used Fairclough’s Critical Discourse Analysis framework to reveal power dynamics in language, in conjunction with theme interpretation. Purposive sampling was used to identify critical excerpts that emphasize transition, identity, and exclusion. The results indicate that transition is articulated as dehumanization, identity is undermined via fluctuating references and pronouns, and exclusion is perpetuated through geographical restriction and suppression. The findings suggest that Kafka’s vocabulary reflects actual discursive practices of exclusion in the real world. The research advocates for the implementation of discourse analysis on extensive literary and social texts, the execution of cross-cultural translation studies, and the connection of literary discourse with current matters of identity politics, migration, and social exclusion. Keywords: Discursive representations, Discriminatory behaviors, Critical Discourse Analysis, Identity, Literary and social texts